Pengaruh Gaya Kepemimpinan dan Motivasi Terhadap Kinerja Karyawan Pada BPJS Ketenagakerjaan Se-Malang Raya - Faris Eka Wahyudi; Achmad Zaki (Jurnal Bisnis Islam dan Kewirausahaan, 2022)
This study aims to determine and analyze the influence of leadership style and motivation on employee performance at BPJS Ketenagakerjaan in Malang Raya. The population in this study were 70 people, the sample used was 41 people. Data collection techniques used in this study were observation, interviews, documentation and questionnaires. The analytical method in this research is a quantitative method. The data analysis technique used in this study is multiple linear regression using the SPSS version for windows program. The results of this study indicate that the first partial leadership style has a significant effect on employee performance. Second, partially motivation has no significant effect on employee performance. Third, simultaneously leadership style and motivation have a significant effect on employee performance